(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Surgery is one of the major and complex medical procedures which can save the patient’s life if performed properly. However, negligence and carelessness during surgical procedures will lead to deterioration of the patient’s health. One of the major challenges that patients often face after surgery is surgery-related infections that can even lead to the death of the patient, but these infections can be prevented and/or treated with appropriate antibiotics.